Ecological and Economical Impact of Riverside Stabilization With Poplar Based Agroforestry - Dhiman, R. C. (Indian Forester, 2023)
This paper presents poplar based agroforestry approach to stabilize eroding riverside of Gola River in Uttarakhand. The technique involved growing of vegetable plants and fruit vines (locally called â€œPallage Cultivationâ€) in trenches made on sandy river beds and simultaneously planting of poplar saplings. Pallage crops grown during the first two years of poplar growth were tomato, capsicum, bitter guard, egg guard, cucumber, squash gourd, pumpkin, water melon, and musk melon; and poplar was grown up to 6 years. Crop harvest yielded 80 qtl and 60 qtl vegetable and fruits per acre during first and second year respectively and final tree harvest yielded 612 qtl fresh wood/acre. It provided a benefit: cost ratio of 2.58 which is much better for such less productive sandy river beds. The practice helped in carbon sequestration of 14.57tC/acre, increased soil arrest inside poplar plantations and in stabilizing river banks along the water flow in the tried locations.